Glucagon and alpha-cells as a novel therapeutic target in the management of diabetes mellitus - Nina Alexandrovna Petunina; Lyubov' Valentinovna Trukhina; Elena Igorevna Sinicyna; Marina Vladimirovna Shestakova (Сахарный диабет, 2013)
For the past several years, a number of studies addressed glucagon and its role in glycemic homeostasis and the development of diabetes mellitus. Current review discusses basic developmental stages of pancreatic islets with special regard for the role of beta-cells and basic mechanisms of glucagon function. We also highlight promising approaches to diabetes compensation based on adjustment of glucagon secretion.